(3EJaGb GdJMcje ai efGRYGJ GdTQcGJ (B/ s - (3MGJe QVG GdSjO YHOGdMejOs; (3SGei YHOGdHGbi CHhUGdM s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3dbO XgQJ acQI GdJMcje chSjdI daV GdefGRYGJ efP hbJ Whjd(B: (3EdG Cf Jdc GdacQI aj HOGjI fTCJgG cGfJ JKjQ JNha GdbVGA NTjI SdH LRA ef GNJUGUg(B: (3hcPdc cGf jfXQ Edi GdJMcje ef LGfH GdeJbGVjf HJMaX hJQOO(B: (3hcGf ef GdUYH EbfGYge HGddLhA Edi gPG GdWQjb deG JQSN dOjge ef ehQhK KbGaj jJeKd aj GdfXQ Edi bVGA GdOhdI Ydi Cfg GdCbOQ Ydi EbGeI GdYOd Hjf GdfGS dJNUU GdbVGI aj eLGd GdbGfhf GdPj jaUdhf HehLH CMcGeg aj GdefGRYGJ GdJj JWQM Ydjge hJeJYge HSdWGJ YGeI JSgd hJjSQ JfajP GdCMcGe GdJj jUOQhfgG Ohf GdMGLI Edi GddLhA dLgI CNQi dJSGYOge aj Pdc(B: (3hgPG Ydi YcS GdMGd HGdfSHI ddJMcje GdPj jMJGL Edi GdbVGA OGFekG dhVY Mceg ehVY GdJfajPs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2013s
(3HHdjhLQGajG(B: (3UaMGJ (B321-340s
Keywords: (3GdbGfhf GdYGes; (3Mb GdTQcGJ aj EHQGe GJaGb GdJMcjes; (3GdJMcje GdELHGQj aj efGRYGJ TQcGJ GdbWGY GdYGes; (3GdTQcGJ GdNGVYI ddJMcje GdGNJjGQjs; (3GdJMcje hbGfhf GdeMGce GdGbJUGOjI Qbe (B120 (3dSfI (B2008s; (3GdJMcje hGdbGfhf Qbe (B10 (3dSfI (B2009s; (3GJaGb GdJMcje GdhGQO aj YbO GdTQcIs; (3GJaGb GdJMcje GdhGQO aj YbO Hjf GdTQcI hGdZjQ s; (3EHQGe GJaGb GdJMcje eY TQcI JfJej deLehYI TQcGJs; (3GdefGRYGJ GdbGHdI ddJMcjes; (3bGHdjI GdfRGY ddJMcje CKfGA MjGI GdTQcIs; (3bGHdjI GdfRGY ddJMcje aj eQMdI GfbVGA GdTQcIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes